Faktor Risiko Diare Akut pada Balita - Hannif Nenny Sri Mulyani, Susy Kuscithawati (Berita Kedokteran Masyarakat (BKM), 2011)
Risk Factors of Acute Diarrhea in Under fivesBackground: Diarrhea is a health problem particularly in developing countries such as Indonesia. The disease is the main cause of mortality in fewer than fives after perinatal and acute respiratory tract infection (ARI). Data of Basic Health Research 2007 showed diarrhea caused mortality in fewer than fives as much as 25.2%. In Yogyakarta Municipality the prevalence of diarrhea at health centers and hospitals in 2009 was in the second rank after ARI with as many as 16,604 cases and the prevalence was 3.6%. Diarrhea is a disease transmittedoro-faecal; therefore it can be transmitted in many ways among others is through polluted water (water borne).Objective: To identify association between bacteriological qualities of clean water, clean water facilities, family toilet, individual hygiene of mother (caregiver) and behavior in boiling drinking water and acute diarrhea in under fives at Yogyakarta Municipality.Method: The study is a case control study undertaken at Yogyakarta Municipality with as many as 250 people comprising 125 cases and 125 controls, were used to univariate, bivariate and multivariate analysis techniques.Results: The result of multivariate analysis showed that individual hygiene (OR=2.16; p=0.010) and clean water facilities (OR=2.10, p=0.022) were the factorsConclusion: There was association between individual hygiene, risk of clean water facilities and the prevalence of acute diarrhea in under fives.Keywords: acute diarrhea, risk factors, underfives